'Message to Dentist': Facilitating Communication with Dentally Anxious Children - Helen Rodd; Laura Timms; Fiona Noble; Sarah Bux; Jenny Porritt; Zoe Marshman (MDPI AG, 2019)
Dental anxiety affects children worldwide and can have negative consequences on oral health. This study aimed to evaluate a novel communication aid ‘message to dentist’ (MTD), as part of a wider cognitive behavioural therapy approach to reduce dental anxiety in young patients. Dentally anxious children, aged 9−16 years, were invited to complete the MTD proforma, before and following their course of treatment. They scored how worried they were and their anticipated pain levels on a scale of 1−10 (10 being the worst outcome). They also wrote down their coping plans and post-treatment reflections. One hundred and five children, from a UK general dental practice and a hospital clinic, were included. They had a mean age of 11.6 years, and 65% were female. There was a significant reduction in self-report worry (from 4.9 to 2.1) and anticipated pain (from 5.1 to 2.0) scores (p < 0.05, paired t-test). Many children (30%) used listening to music/audiobook as a coping strategy. Thematic analysis revealed concerns around pain, uncertainty, errors and specific procedures. The MTD proforma proved an effective means of facilitating communication between anxious children and the dental team, allowing them to identify their worries and make personalised coping plans.